EVALUASI KINERJA PINTU AIR MANGGARAI UNTUK PENGENDALIAN BANJIR JAKARTA PUSAT - , Mursid ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Located in the northern coastal region of the western part of Java Island with most of the area is below sea tide level, Jakarta always suffer from flood during rainy season. The flood is an overflowing river that cross several areas of the city, one of them is Ciliwung River. Manggarai Flood Gate is located on the downstream side of Ciliwung River that control the water flow of Ciliwung River to West Flood Canal and to the Ciliwung Lama River. The flood gate on Ciliwung Lama is cannot be opened during major flood. It is only opened for certain times when there is a small discharge flow for river maintenance and discharge. Therefore, it is necessary to evaluate performance of the two flood gates to reduce the burden of West Flood Canal, also for flood control in Central Jakarta area. This research conducts analysis of hydrology and hydraulics. The hydrologic analysis uses average daily rainfall data of Ciliwung Catchment Areas with control point at Kalibata Bridge, flood hydrograph is calculated with Nakayasu synthetic unit hydrograph methods. Hydraulics analysis is performed with HEC - RAS 4.1.0 software. The hydraulics analysis consists of two simulations, i.e. (1) Simulation model calibration of Ciliwung River downstream area on the existing condition based on flood on February 4, 2007 (Q 2007), and (2) The simulation is performed in several periods with second scheme, that is the first model branches out to the Ciliwung Lama River. Each flood scenario has several simulation variations on gate elevation height of Ciliwung Lamaâs flood gate from 0.50 m to 8.00 m, with 0.50 m openings intervals. Each simulation results are evaluated to obtain the maximum gate elevation height that will not cause flood along the Ciliwung Lama River The hydrologic analysis result for maximum daily rainfall is using Log Pearson III distribution and maximum hidrogaf unit value is 3.34 m3/sec. Flood water level (m.a.b) from hydraulics model calibration analysis simulation result is compared to the m.a.b test result on observation point in 2007, and the result shows that the difference of m.a.b. is relatively small, which is below 10 %. The evaluation of simulation result on maximum gate elevation height height at Ciliwung Lama shows that based on flood in Q2007 and period of 2, 5, 10, 20, 50 and 100 years, the maximum height for gate elevation on Ciliwung Lama is 4,00 m, 2.50 m, 1.50 m, 1.50 m, 1.00 m, 1.00 m, and 1.00 m. The operational of maximum gate elevation on flood period at the observation points of Kalibata Bridges, MT Haryono Bridge, Casablanca Bridge and Bukitduri Bridge shows that it does not decrease the flood water level, while at the observation points of Slamet Riyadi Bridge, Manggarai Bridge, BKB flood gate and RS 0000 Pasar Rumput shows decrease on flood water level between 0.28 m to 0.74 m.